Case report: Development of vanishing bile duct syndrome in Stevens-Johnson syndrome complicated by hemophagocytic lymphohistiocytosis - Lin, Wan-Chen; Hsieh, Tyng-Shiuan; Chu, Chia-Yu (Frontiers in Medicine, 2022)
Background Vanishing bile duct syndrome is a rare drug-induced disease characterized by cholestasis and ensuing ductopenia. Dermatological manifestations of drug hypersensitivity such as Stevens-Johnson syndrome and toxic epidermal necrolysis may also present in such cases. Hemophagocytic lymphohistiocytosis is a hyperimmune response caused by unchecked stimulation of macrophages, natural killer cells, and cytotoxic T lymphocytes. Case presentation We report a severe case who presented with concurrent Stevens-Johnson syndrome and vanishing bile duct syndrome complicated by hemophagocytic lymphohistiocytosis after the ingestion of non-steroidal anti-inflammatory drugs. Despite the fact that improvements in vanishing bile duct syndrome can be assumed when combining the clinical lab data clues, as well as repeated liver biopsies showing recovering ductopenia, the patient developed hypovolemic shock combined with septic shock episodes and died on day 236. Conclusion To our knowledge, this is the fifteenth report of vanishing bile duct syndrome associated with Stevens-Johnson disease or toxic epidermal necrolysis. Mortality rate remains high without treatment guidelines established due to the rarity and heterogenicity of the population. Further studies are needed to identify possible risk factors, prognostic indicators, and the standard of care for vanishing bile duct syndrome associated with Stevens-Johnson disease or toxic epidermal necrolysis.